Preparation method of composite powder carrier magnetic biochar material applied to sewage treatment
Through co-pyrolysis method and ball mill modification technology, composite powder magnetic biochar material was prepared, which solved the problems of small adsorption capacity, poor catalytic performance and difficult recovery of biochar in wastewater treatment, and achieved various uses of the material and Efficient recycling.
Patent Information
- Application Number
- CN202411420353.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-02-25
AI Technical Summary
The existing biochar has small adsorption capacity, no catalytic properties, and is not easy to separate and recover in terms of organic pollution in water bodies, which limits its application in sewage treatment.
The composite powder magnetic biochar material is generated in one step by co-pyrolysis method, and iron is loaded on the surface of the biochar and vulcanized. Combined with ball milling modification, the specific surface area and pore volume of the material are improved, and its adsorption, catalytic and magnetic responsiveness are enhanced.
It realizes a variety of uses of the material, including adsorption, catalysis, microelectrolysis and microbial fortification, has magnetic responsiveness and is easy to recover, reduces water treatment costs, and extends the service life of the material.
Smart Images

Figure CN119500064A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of waste resource utilization and water treatment, and specifically relates to a method for preparing a composite powder carrier magnetic biochar material which has multiple uses, is simple to make and is applied to sewage treatment. Background Art
[0002] In recent years, water supply and wastewater treatment standards have become increasingly stringent. Organic pollutants in water bodies are highly toxic and pose high environmental risks, posing a huge threat to humans and the ecological environment. Therefore, people have gradually paid attention to technologies that can treat difficult-to-degrade organic pollutants in water or wastewater.
[0003] Biochar is a solid carbon-based material made by pyrolyzing biomass in an anaerobic environment. Its raw materials come from a variety of sources, including wood chips, bamboo chips, sludge, coconut shells, straw, etc. It can be used as an adsorbent, catalyst, and microbial biofilm carrier to remove organic pollutants from water bodies. However, the adsorption performance of biochar is affected by many factors, such as the type and number of functional groups on the surface of biochar, the specific surface area of unmodified biochar will affect the adsorption capacity of biochar, and the pore size and porosity will affect the mass transfer rate of pollutants on the surface and inside of biochar, which will limit the treatment efficiency of biochar in practical applications. In terms of the catalytic performance of biochar, unmodified biochar is not efficient in catalytic reactions due to its insufficient surface active sites. In addition, unmodified biochar lacks magnetism or other properties that facilitate recovery, and is difficult to separate and recover from the reaction system after the catalytic reaction, which limits its application in continuous reactions or industrial production.
[0004] To address these problems with unmodified biochar, modification is usually used to optimize the pore structure of biochar, increase surface functional groups, introduce active metal centers, etc., in order to overcome the shortcomings of unmodified biochar and enhance its application as a catalyst, micro-electrolysis material, and adsorption material to effectively remove organic pollutants.
[0005] In the prior art, physical modification of biochar includes steam activation, ultraviolet radiation, ball milling, freeze-thaw cycle, etc. Chemical modification can be divided into acid modification, alkali modification, organic agent modification, metal salt or metal oxide modification, nanomaterial modification, plasma modification, etc. according to the different modification agents. Biological modification usually promotes the attachment and reproduction of microorganisms on biochar through the nutrients contained in biochar and the developed pore structure. Chemical modification is the most common biochar modification technology. By selecting appropriate modification methods and modification agents used, biochar can have better performance. For example, iron salt modification can generate Fe3O4 or γ-Fe2O3 on the surface of biochar to enhance the magnetism of biochar, which is convenient for later separation and recycling, and at the same time introduces other non-metallic heteroatoms to change the chemical properties of the material. For example, S doping can destroy the charge balance of the covalent carbon electron system and affect the porous structure of biochar.
[0006] At present, many literatures have been reported on metal loading, especially iron loading, on biochar to make the biochar surface have more active metal centers and magnetic separation properties. However, in many reported literatures, most material preparation methods require the use of raw materials to prepare biochar first, and then metal loading on the biochar, which is a cumbersome process. If zero-valent iron needs to be loaded on the surface of biochar, it is necessary to add reducing agents such as ascorbic acid, sodium borohydride, potassium borohydride, etc., and provide an anaerobic environment for protection during the preparation process. The preparation conditions and processes have room for optimization. Summary of the invention
[0007] The purpose of the present invention is to prepare a composite powder carrier magnetic biochar material for sewage treatment in a simple and low-cost manner, which is used to solve the problems of organic pollution in water bodies and the small adsorption capacity, lack of catalytic performance, and difficulty in separation of unmodified and unmetal-loaded biochar.
[0008] In one aspect, the present invention provides a method for preparing a composite powder carrier magnetic biochar material for sewage treatment, comprising the following steps: 1) Dry the sawdust with a particle size of less than 100 mesh to constant weight.
[0009] 2) Weigh a certain amount of metal salt reagent, add it into water to fully dissolve it, then add dried sawdust and stir evenly.
[0010] 3) Dry and grind the obtained sawdust, metal salt solution and other supplementary materials, place them in a sealed container for anaerobic pyrolysis, and after the pyrolysis is completed, obtain composite powder magnetic biochar material by ball milling.
[0011] Preferably, the drying temperature in step (1) is 80-100° C. and the drying time is 8 h.
[0012] Preferably, the metal salt reagent includes ferrous sulfate or its hydrate and solvate; the added amount of ferrous sulfate or its hydrate and solvate is 20-30% of the mass of the sawdust (calculated as iron element).
[0013] Preferably, the metal salt reagent further includes copper sulfate or its hydrate and solvate; the mass ratio of ferrous sulfate to copper sulfate is 5:1 (calculated in terms of iron element and copper element).
[0014] Preferably, the ferrous sulfate is ferrous sulfate heptahydrate, and the copper sulfate is copper sulfate pentahydrate.
[0015] The metal salt reagent in step (2) is ferrous sulfate heptahydrate (partially including copper sulfate pentahydrate), so that the prepared material contains iron and sulfur elements. When used as a micro-electrolysis material or a biofilm carrier, only ferrous sulfate heptahydrate is used. When the prepared composite powder carrier magnetic biochar material is used as a catalyst, a small amount of copper sulfate pentahydrate is added, and the amount added is determined according to the mass ratio of the metal element iron: copper = 5:1.
[0016] Preferably, other supplementary materials are added together with the dried sawdust in step 3); the other supplementary materials are one or two of municipal sludge, iron powder or coal powder; the amount of the other supplementary materials added is 0-40% of the mass of the sawdust. In some specific embodiments, one or two of them are added during preparation, or none of them are added.
[0017] Preferably, the stirring time in step 2) is 3-5 hours and the rotation speed is 300-500 rpm.
[0018] Preferably, in step 3), the temperature raising procedure of the anaerobic pyrolysis is to raise the temperature to 200-300°C at a heating rate of 5°C / min and keep the temperature for 0.5-1h, and then raise the temperature to 700-1000°C at the same rate of 5°C / min and keep the temperature for 1-3h.
[0019] Preferably, the drying and grinding procedure in step 3) is to dry at 60-100°C for 1-4h until semi-dry, break up and grind with a mortar, and then dry at 120-180°C for 0.3-1h. Furthermore, in step (3), the temperature and time for drying the mixed solution to semi-dryness are 80-100°C, the drying time is 1-3h, then break up and grind, and then dry at 120-160°C for 0.3-0.5h.
[0020] Preferably, in step 3), the pyrolysis product is taken out when the temperature drops below 50° C., ball-milled for 0.5 h, and passed through a 300-mesh sieve to obtain a composite powder magnetic biochar material.
[0021] Preferably, the concentration of ferrous sulfate in the mixed solution in step 2) is 41 g / L (in terms of iron element). In actual operation, there are no other requirements for the amount of water used and the concentration of the metal salt when preparing the mixed solution, as long as the above substances can be stirred evenly.
[0022] Another aspect of the present invention further provides a composite powder magnetic biochar material prepared by the above-mentioned preparation method.
[0023] The present invention uses biochar as a carrier and iron as a loaded metal for removing organic pollution in water bodies. The material preparation method is simple, the raw material cost is low, and there is no need to use controlled agents to prepare reducing metals or metal sulfides. It can be used as a heterogeneous Fenton and persulfate catalytic oxidation to deeply treat organic pollution in water bodies. The prepared composite powder magnetic biochar material has magnetic responsiveness, which can facilitate catalyst recovery to reduce water treatment costs.
[0024] Biochar has a porous structure, a large specific surface area, and abundant surface functional groups, which can be used to treat organically polluted wastewater, and can also be used as an excellent metal loading carrier and microbial biofilm carrier. Zero-valent iron can also be used to treat organically polluted wastewater, but zero-valent iron itself is prone to agglomeration and passivation during the reaction. The present invention uses a co-pyrolysis method to complete the iron loading modification of biochar and makes the loaded iron sulfided, thereby achieving chemical modification of biochar, increasing the metal active sites on the surface of biochar to improve micro-electrolysis and catalytic performance, and solving the problems of iron agglomeration and passivation, and the magnetic responsiveness of the material. The prepared biochar is physically modified by ball milling to increase the specific surface area and pore volume of biochar, which, on the one hand, enhances the adsorption capacity of biochar for organic matter and the load strengthening capacity for microorganisms, and on the other hand, makes the metal reducibility of the biochar surface load stronger. In addition, the main component of the material prepared by this preparation method is iron carbon, so it also has micro-electrolysis capability.
[0025] The present invention also relates to the practical application of the aforementioned composite powder magnetic biochar, and provides corresponding embodiments for the catalytic oxidation ability, micro-electrolysis ability, adsorption ability, and microbial enhancement ability of the material.
[0026] The present invention has the following beneficial effects: (1) Compared with the traditional two-step method of first pyrolyzing the biochar raw material to generate biochar and then modifying it, the present invention adopts a co-pyrolysis method to generate a composite powder magnetic biochar material in one step and simultaneously completes the metal loading and its sulfurization modification, and prepares the composite powder magnetic biochar material by coupling ball milling modification. The transition metal is reduced by the reducing gas generated by the pyrolysis of the biochar raw material, without the need to add regulated reducing agents such as sodium borohydride, and without the need to provide nitrogen protection, which has the advantages of simple production process and low cost.
[0027] (2) The material prepared by the present invention has multiple uses such as adsorption, micro-electrolysis, catalysis, and microbial enhancement. It can be used as both an adsorbent and a catalyst. In addition, since the iron salt modification has magnetic responsiveness, it can be separated and recovered by magnetism, which is convenient for reuse.
[0028] (3) The material prepared by the present invention is reusable. The surface of the iron particles loaded on the biochar is sulfided to generate iron sulfide (FeSx). The sulfided iron is not easily passivated, thereby extending the service life of the material.
[0029] (4) The raw materials used to prepare biochar in the present invention are by-products or wastes from other production links, which has the advantage of resource utilization and is in line with the concept of sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is the preparation process of the composite powder magnetic biochar of the present invention.
[0031] Figure 2 This is the material micro-electrolysis effect of Example 3.
[0032] Figure 3 This is the microbial enhancement effect of Example 4.
[0033] Figure 4 is a SEM image of the material prepared in Example 1.
[0034] Figure 5 This is the SEM image of the material prepared in Example 2.
[0035] Figure 6 is the XRD pattern of the materials used in the examples.
[0036] Figure 7 This is the hysteresis loop diagram of the material used in the embodiment. As shown in the figure, the saturation magnetization intensity is 20.41emug -1 , indicating that the material has magnetic responsiveness and magnetic separation capabilities, and can be easily recycled in water treatment processes. DETAILED DESCRIPTION
[0037] In order to further understand the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0038] Unless otherwise specified, the experimental methods used in the following examples are generally carried out under conventional conditions or under conditions recommended by the manufacturers.
[0039] Example 1 The material is used to catalyze persulfate oxidation to treat chlorobenzene simulated wastewater.
[0040] The preparation process of the present invention is as follows Figure 1 shown.
[0041] (1) The sawdust was dried at 80°C for 8 h, and then a mixed solution was prepared according to the mass ratio of sawdust (particle size less than 100 mesh): ferrous sulfate heptahydrate (in terms of iron): copper sulfate pentahydrate (in terms of copper) = 100:25:5, so that the concentration of ferrous sulfate in the mixed solution was 200 g / L, and the concentration of iron was 41 g / L. Stirring was carried out at a stirring speed of 300 rpm for 5 h, and then dried at 80°C for 3 h until semi-dry, ground with a mortar, and then dried at 150°C for 0.5 h. After drying, the above materials were added to a crucible for anoxic pyrolysis. The pyrolysis procedure was to heat to 300°C within 1 h, keep warm for 1 h, and then heat to 900°C at a heating rate of 5°C / min, and then keep warm at 900°C for 2 h to complete the co-pyrolysis. After cooling, the mixture was taken out and ball milled for 0.5 h to obtain a granular composite powder magnetic biochar material 1 (referred to as material 1) with a dark black appearance and light texture. Through EDS element analysis, the composition of the composite powder magnetic biochar material 1 is as follows: in terms of weight percentage, the carbon content of the material is 64.84%, the oxygen content is 5.01%, the iron content is 16.07%, the sulfur content is 10.70%, and the copper content is 3.38%. In terms of atomic percentage, the carbon content is 84.53%, the oxygen content is 4.90%, the iron content is 4.51%, the sulfur content is 5.23%, and the copper content is 0.83%.
[0042] (2) Take 40 mL of 6 mg / L chlorobenzene simulated wastewater and place it in a 40 mL brown screw-mouth bottle with a polytetrafluoroethylene / silicone gasket cap, add 0.02 g of the material obtained in step 1), add 2.5 mM PDS (sodium persulfate), and react at 25 °C and 180 rpm for 1 h. After the reaction is completed, use a 2 mL syringe to pierce the bottle cap to extract 2 mL of solution, filter it with a 0.22 μm filter head, add sodium thiosulfate to terminate the reaction, and then perform PDS and chlorobenzene concentration detection.
[0043] The results showed that the final activation rate of PDS was 97% and the degradation rate of chlorobenzene was 99%, which proved that the material has the ability to catalyze the oxidation and degradation of chlorobenzene by persulfate.
[0044] Example 2 The material is used to adsorb the influent of a sewage treatment plant, the main types of which are industrial wastewater and domestic sewage. To prevent the material from playing a micro-electrolysis role, the pH is not adjusted and aeration is not performed.
[0045] (1) The sawdust was dried at 80°C for 8 hours, and then a mixed solution was prepared according to the mass ratio of sawdust (particle size less than 100 mesh): ferrous sulfate heptahydrate: municipal sludge = 100:20:30, so that the concentration of ferrous sulfate in the mixed solution was 200g / L, and the concentration of iron was 41g / L. Stirring was carried out at a stirring speed of 300rpm for 5 hours, and dried at 80°C for 3 hours until semi-dry, ground with a mortar, and then dried at 150°C for 0.5 hours. After drying, the above materials were added to a crucible for anoxic pyrolysis. The pyrolysis program was to heat to 300°C within 1 hour, keep warm for 1 hour, and then heat to 900°C at a heating rate of 5°C / min, and then keep warm at 900°C for 2 hours to complete the co-pyrolysis. After cooling, the mixture was taken out and ball milled for 0.5 hours to obtain a dark black granular composite powder magnetic biochar material 2 (hereinafter referred to as material 2). Through EDS element analysis, the composition of the composite powder magnetic biochar material 2 is as follows: in terms of weight percentage, the carbon content is 35.17%, the oxygen content is 3.04%, the iron content is 40.80%, and the sulfur content is 20.98%. In terms of atomic percentage, the carbon content is 65.02%, the oxygen content is 4.23%, the iron content is 16.22%, and the sulfur content is 14.53%.
[0046] (2) The pH of the sewage plant influent was 6.91, the COD concentration was 168.09 mg / L, the ammonia nitrogen was 25.28 mg / L, the total nitrogen was 29.96 mg / L, and the total phosphorus was 3.7 mg / L. 200 mL of the sewage plant influent was placed in a conical flask, and the addition amount of material 2 was 1 g. The mixture was stirred at a frequency of 500 rpm. After 1 hour of adsorption treatment, the pH was 8.6, the COD was 63.52 mg / L, the ammonia nitrogen was 22.84 mg / L, the total nitrogen was 24.56 mg / L, and the total phosphorus was 0.6 mg / L. The removal effect on COD and total phosphorus was 62%, and the removal rate of COD and total phosphorus was 84%. COD was removed because of the adsorption of biochar, and total phosphorus was removed because the metals loaded on the biochar formed precipitation with phosphate ions.
[0047] It is proved that the material prepared by this preparation method has good COD adsorption performance and total phosphorus removal performance. The material is used for micro-electrolysis of sewage plant influent, the main types of which are industrial wastewater and domestic sewage. Material 2 was obtained by preparing the material according to the method of Example 2. Take a 1L measuring cylinder and add 0.6L of sewage plant influent, and add 1.8g of material under aeration and oxygenation. After aeration for 16 hours, sample and test. After the reaction is completed, the material is separated, and 0.6L of sewage plant influent is added again, and the experiment is repeated 5 times. After the first aeration reaction, pour out the supernatant after precipitation, retain the material, continue to add water and aerate for 16 hours, then take samples to determine indicators such as COD, ammonia nitrogen and total phosphorus, and calculate the removal rate of COD, ammonia nitrogen, total nitrogen and total phosphorus in sewage by micro-electrolysis of the material. The calculation results show that the contents of COD, ammonia nitrogen, total nitrogen and total phosphorus are significantly reduced, and repeated use has little effect on its micro-electrolysis performance. The specific results are shown in Figure 2 .
[0048] The control group was aerated without adding materials. The pH before and after aeration increased from the initial 6.91 to 7.03, COD increased from 396.09 mg / L to 392.20 mg / L, and NH4 + -N decreased from 28.28mg / L to 17.95mg / L, TN decreased from 39.31mg / L to 35.09mg / L, and TP decreased from 5.70mg / L to 5.44mg / L. Aeration only had a certain effect on the removal of ammonia nitrogen. The above results show that the material has good micro-electrolysis performance and can be reused.
[0049] Example 4 The material is used to strengthen the activated sludge treatment of sewage plant influent, the main types of which are industrial wastewater and domestic sewage. Material 2 was obtained by preparing the material according to the method of Example 2. Take 2 1L measuring cylinders and add aeration heads, and add 800mL of the water plant aerobic pool mud and water mixture (sludge concentration is about 10g / L) respectively. One is used as the control group, and the other is added with 5g / L of material as the experimental group. Take the influent of the sewage plant, operate the biochemical reactor in the SBR mode, and set the residence time to 23h. After stopping aeration for 1 hour every day, pour out half of the supernatant, add 400ml of sewage, and then continue to operate in SBR mode for 1-2 weeks, measure the changes in SV30 (sludge settling ratio after 30min of sedimentation), and detect the indicators such as effluent COD, ammonia nitrogen, total nitrogen and total phosphorus at the same time, and compare the removal rates of sewage COD, ammonia nitrogen, total nitrogen and total phosphorus after adding the materials. See the specific results for details. Figure 3 , after adding material 2, the sludge settling performance was significantly improved ( Figure 3 f), the effluent COD and total phosphorus decreased significantly compared with the control group, proving that the material has good compatibility with activated sludge and is beneficial to improving the biochemical effect.
[0050] Comparative Example 1 Comparative Example 1: Nano-zero-valent iron copper-loaded biochar was prepared by liquid phase reduction method (from literature). First, the biochar obtained by calcination at 800°C was stirred in 200 mL of a certain concentration of CuCl2⋅2H2O solution for 12 h; then, it was stirred in 200 mL of a certain concentration of FeCl3⋅6H2O solution for another 12 h; then, after removing dissolved oxygen, the mixed solution was stirred by a mechanical stirrer under N2 atmosphere, and NaBH4 solution was continuously dripped at a rate of two drops per second; finally, the final solid was filtered, washed with deionized water and ethanol, and then dried in a vacuum at 60°C.
[0051] Comparative Example 2 Comparative Example 2: Carbon and sulfur co-doped micron zero-valent iron (from the literature) was prepared by ball milling. First, trace iron, sulfur and graphite were weighed in different proportions and placed in 4 100mL hard stainless steel cans, each of which contained 50 zirconium oxide balls (6mm in diameter), which were combined and sealed with nitrogen; then, they were placed in a planetary ball mill, the milling frequency was set to 400Hz (about 600rpm), and the milling was continued for 20 hours; finally, the CS-mZVIbm particles were separated to obtain the finished product. Compared with Comparative Examples 1 and 2, the present invention adopts both ball milling and co-pyrolysis to prepare composite powder magnetic biochar materials, without the need to provide a nitrogen protective atmosphere, a reducing agent, and other prefabricated products (such as graphite, fired biochar), and only needs to soak the sawdust and the supplementary materials in a metal salt solution and stir evenly, dry and pyrolyze, and then perform ball milling modification to obtain the target product. Compared with Comparative Examples 1, 2, and other prior arts, the preparation method of the composite powder magnetic biochar material of the present invention is simple to make and low in cost, and has a wide range of uses.
[0052] The present invention further characterizes the materials obtained in Examples 1 to 4. The SEM of Material 1 is as follows: Figure 4 The SEM of material 2 is shown in Figure 5 As shown, the granular and flake-like substances with polycrystalline faces on the surface of the material are the metals loaded thereon. It can be seen that there are two ways of combining iron and biochar: physical combination and chemical combination. Figure 6 The XRD patterns of the materials obtained in Example 1 and Examples 2-4 are shown in the figure, respectively. The compounds contained in the materials can be determined from the diffraction angle values. Figure 7 This is the hysteresis loop diagram of the material obtained in Example 2. As shown in the figure, the saturation magnetization intensity is 20.41emug -1 , indicating that the material has magnetic responsiveness and magnetic separation capabilities, and can be easily recycled in water treatment processes.
[0053] After testing, the obtained composite powder magnetic biochar material can effectively catalyze the oxidation of PDS to remove chlorobenzene, as shown in Example 1. It still has an adsorption effect, as shown in Example 2. It has a micro-electrolysis effect, as shown in Example 3. It has a microbial enhancement effect, as shown in Example 4.
[0054] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For the technical personnel in this field, the present invention can have various changes and variations. Any modification, equivalent replacement, improvement, etc. made to the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a composite powder carrier magnetic biochar material for sewage treatment, characterized in that: The steps include: 1) Dry the sawdust with a particle size of less than 100 mesh to constant weight; 2) Weigh a certain amount of metal salt reagent, add it into water to fully dissolve it, then add dried sawdust and stir evenly; 3) Dry and grind the obtained sawdust, metal salt solution and other supplementary materials, place them in a sealed container for anaerobic pyrolysis, and after the pyrolysis is completed, obtain composite powder magnetic biochar material by ball milling.
2. The preparation method according to claim 1, characterized in that: The metal salt reagent includes ferrous sulfate or its hydrate and solvate; the added amount of ferrous sulfate or its hydrate and solvate is 20-30% of the mass of the sawdust (calculated as iron element).
3. The preparation method according to claim 2, characterized in that: The metal salt reagent also includes copper sulfate or its hydrate and solvate; the mass ratio of ferrous sulfate to copper sulfate is 5:1 (calculated in terms of iron element and copper element).
4. The preparation method according to claim 1, characterized in that: In the step 3), other supplementary materials are added together with the dried sawdust; the other supplementary materials are one or two of municipal sludge, iron powder or coal powder; and the addition amount of the other supplementary materials is 0-40% of the mass of the sawdust.
5. The preparation method according to claim 1, characterized in that: The stirring time in step 2) is 3-5 hours, and the rotation speed is 300-500 rpm.
6. The preparation method according to claim 1, characterized in that: In the step 3), the temperature raising procedure of the anaerobic pyrolysis is to raise the temperature to 200-300°C at a heating rate of 5°C / min and keep the temperature for 0.5-1h, and then raise the temperature to 700-1000°C at the same rate of 5°C / min and keep the temperature for 1-3h.
7. The preparation method according to claim 1, characterized in that: The drying and grinding procedure in step 3) is to dry at 60-100° C. for 1-4 hours until half dry, break up and grind with a mortar, and then dry at 120-180° C. for 0.3-1 hour.
8. The preparation method according to claim 1, characterized in that: In step 3), the pyrolysis product is taken out when the temperature drops below 50° C., ball-milled for 0.5 h, and sieved through a 300-mesh sieve to obtain a composite powder magnetic biochar material.
9. The preparation method according to claim 1, characterized in that: The concentration of ferrous sulfate in the mixed solution in step 2) is 41 g / L (in terms of elemental iron).
10. The composite powder magnetic biochar material prepared according to the preparation method according to any one of claims 1 to 9.